Purification, Beneficiation and Activation of Iraqi Attapulgite Clay Mineral - Nadhum Gharb Taher (Journal of Global Pharma Technology, 2016)
This study aimed to obtain a pure activated Attapulgite mineral to use it as adsorption surface in our search, because of its importance in removing impurities, desulfurization, decolorizing, neutralizing, and deodorizing of petroleum fuel. The large specific surface area and high cation exchange capacity of Attapulgite make it suitable in our work. However, the adsorption capacity of natural Attapulgite is limited, new activated pure Attapulgite clay was synthesized by purification and beneficiation Attapulgite to increase its ability to use in our search and other various fields, particularly in the petroleum refining. The pure activated calcined Attapulgite characterized by FT-IR spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy (SEM). Attapulgite mineral was purified by floatation with the dispersed swelled sodium methyl acrylate granules leaving other impurities of clay mineral and sand in the bottom of the vessel. Therefore many peaks in FT-IR spectrum were disappeared comparing with the FT-IR spectrum of crud material. The disappearance of calcium carbonate peaks at (29.3556) 2 Ɵ was observed due to the purification of Attapulgite from other mineral impurities using sodium methyl acrylate, while the peaks of the Attapulgite remained clear. SEM images of pure activated Attapulgite show a high resolution with an accurate vision of needle- shaped structure.Keywords: Desulfurization; Beneficiation; Attapulgite; Adsorption; Surface.